Healthcare-Related Costs Associated with Switching Subcutaneous Tumor Necrosis Factor-α Inhibitor in the Treatment of Inflammatory Arthritis: a Retrospective Study - Dalén, Johan (Adv Ther, 2020)
INTRODUCTION: Subsequent lines of subcutaneous tumor necrosis factor alpha inhibitor (SC-TNFi) treatment may be well motivated in the management of rheumatoid arthritis (RA), ankylosing spondylitis (AS), and psoriatic arthritis (PsA)—collectively named inflammatory arthritis (IA). However, the costs associated with switching SC-TNFis are largely unknown. The objective of this retrospective observational study was to explore costs of healthcare resource utilization (HCRU) associated with switching SC-TNFi treatment among biologic-naïve Swedish patients with IA. METHODS: Using population-based register data, adult patients filling prescriptions between May 6, 2010 and December 31, 2014 for an SC-TNFi (adalimumab, etanercept, certolizumab, and golimumab) were included. Patients switching treatment (cyclers) were matched to treatment persistent patients on the basis of propensity score and follow-up time. HCRU-associated costs were captured and compared 12 months before and 12 months after the index date (defined as the date of the switch). RESULTS: A balanced cohort of 594 matched pairs was derived. Prior to the index date, cyclers had significantly higher non-treatment HCRU costs compared to persistent patients ($3815 [3498–4147] vs. $2900; 95%CI [2565–3256]). However, 12 months after the index date, cyclers had significantly increased their non-treatment HCRU costs while persistent patients lowered theirs ($822 [232–1490] vs. $− 313 [− 664–36]). This resulted in a statistically significant difference in difference of $1135 between the groups. CONCLUSIONS: In biologic-naïve patients treated with SC-TNFi for IA, cyclers significantly increased their non-treatment HCRU costs 12 months after switching treatment while persistent patients lowered their costs during the same time period. As these findings indicate that differences in treatment persistence may have an impact on costs, further research utilizing more comprehensive data sources in alternate settings is warranted.